2021
DOI: 10.1038/s41545-020-00095-x
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminarily comparative performance of removing bisphenol-S by ferrate oxidation and ozonation

Abstract: Bisphenol-S (BS) has recently raised public concerns for its adverse effect on the health safety and ecological security. BS concentrations were detected in many water resources, ranging from 10 ng L−1 to 300 μg L−1, so that various purification techniques have been sought to remove BS. This study investigated the performance of ozonation and ferrate oxidation in the degradation of BS since they are both promising oxidants with high redox potential among water treatment chemicals. It was observed that both ozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the last two decades, researchers have examined the oxidation properties of Fe VI O 4 2– with pollutants such as cyanides, sulfides, thiols, phenols, anilines, pharmaceuticals, endocrine disrupting compounds, and other toxins. ,, ,,,, The Hammett relationships were also derived to gain insight into the factors that govern the kinetics of the reactions between Fe VI O 4 2– and pollutants. ,, Transformation products of organic pollutants suggested preferential attacks of Fe VI O 4 2– toward the reduced sulfur (−II) moiety of the molecule with stepwise oxidation to sulfenyl, sulfinic, sulfonic acids, and eventually sulfate. Reactions of phenolic compounds with Fe VI O 4 2– indicated hydroxylation and coupling reactions. , ,,,, Detailed mechanisms have been previously reviewed . In the reaction with the cyanotoxin microcystin-LR (MC-LR), Fe VI O 4 2– carried out hydroxylation of the aromatic ring, the diene, and the double bond of the methyldehydroalanine (Mdha) amino acid residue, followed by the fragmentation of the cyclic MC-LR structure .…”
Section: Ferrate Species (Fevi Fev and Feiv)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, researchers have examined the oxidation properties of Fe VI O 4 2– with pollutants such as cyanides, sulfides, thiols, phenols, anilines, pharmaceuticals, endocrine disrupting compounds, and other toxins. ,, ,,,, The Hammett relationships were also derived to gain insight into the factors that govern the kinetics of the reactions between Fe VI O 4 2– and pollutants. ,, Transformation products of organic pollutants suggested preferential attacks of Fe VI O 4 2– toward the reduced sulfur (−II) moiety of the molecule with stepwise oxidation to sulfenyl, sulfinic, sulfonic acids, and eventually sulfate. Reactions of phenolic compounds with Fe VI O 4 2– indicated hydroxylation and coupling reactions. , ,,,, Detailed mechanisms have been previously reviewed . In the reaction with the cyanotoxin microcystin-LR (MC-LR), Fe VI O 4 2– carried out hydroxylation of the aromatic ring, the diene, and the double bond of the methyldehydroalanine (Mdha) amino acid residue, followed by the fragmentation of the cyclic MC-LR structure .…”
Section: Ferrate Species (Fevi Fev and Feiv)mentioning
confidence: 99%
“…Fe VI O 4 2– has been reported to oxidize a wide range of concerning pollutants. ,, Although successful applications of Fe VI O 4 2– have been demonstrated, progress toward understanding the oxidation mechanisms has been made only in the past few years. ,,,, Studies have been conducted to distinguish the one-electron and two-electron (or oxygen-atom) transfer steps of the oxidative reactions of Fe VI O 4 2– using the redox potentials of the pollutants. This initial understanding revealed that the oxidation capacity of Fe VI O 4 2– (i.e., moles of electron equivalent per mole of oxidant) depends on the involvement of intermediate iron species, Fe V and Fe IV , in the reactions. In other words, the involvement of such high-valent species increases the oxidation capacity of Fe VI O 4 2– .…”
Section: Introductionmentioning
confidence: 99%
“…Instead of AOPs, ferrate is an innovative technology because of its similarly high redox potential compared to those popular AOPs. Ferrate is regarded as a promising degradation technique in water processing because of the dual functions of its properties, i.e., the oxidation and coagulation of various contaminants [5][6][7][8]. The study of ferrate as a water-cleaning reagent has received great interest, and a series of trials on ferrate treatment have been conducted.…”
Section: Introductionmentioning
confidence: 99%